The results of treatment of chronic recurrent aphthous stomatitis by gel containing zero-valent silver - I. A. Artemieva; G. I. Aksenova; I. B. Vasiliev; T. P. Zyubr; V. A. Babkin; L. A. Ostroukhova (Acta Biomedica Scientifica)
The article presents the results of complex treatment of chronic recurrent aphthous stomatitis by methylcellulose-based gel with arabinogalactan biocomposite containing zero-valent silver in nano-valent condition. The gel was applied 3-6 times a day at the prescription of Diquertin 0,06 g 3 times a day and Fibrolar 0,3g 3 times a day. The proposed method of treatment allows to improve the effectiveness of treatment by increasing remission and reducing treatment terms.